Neoliberalism and Control Strategies: the Urban Security Policies in Italy - Ricotta, Giuseppe (PARTECIPAZIONE E CONFLITTO, 2016)
From the early 1990s, In Italy discourses and practices referring to urban security and preven-tion have increased. The purpose of this article is to highlight the specific characteristics of the Italian ap-proach to urban security. Firstly, the strong leadership of local governments in defining the urban security policy, in a conflictual dynamic of national vs local. Secondly, the link between the issue of security and immigration, both at national and local levels. The reconstruction of the history of urban security policies in Italy is aimed at answering the following question: can we interpret the Italian case, despite its national specificity, as coherent with the shift in the culture of control argued by David Garland in relation to the UK and the US contexts? We argue that, also in the Italian context, we witnessed, on one hand, the use of local adaptive policies, in line with neoliberal principles. On the other hand, the rise of punitive populism in the rhetoric and practices, not only at the central State level, but also at local level where adaptive policies were developed together with administrative punitive measures. The conclusions propose a critical ac-count of Italian urban security policies